Analysis of temperature field and effect of cold-formed stainless steel roof panels - Wang, Dayang; Xin, Zhiyong; Wang, Mingming; Ou, Tong; Mao, Jihua; Zhu, Yong; Tan, Jian (Journal of constructional steel research, 2022)
The thermal effects on large-span metal roof systems are significant due to solar radiation. In this paper, the temperature field and variations of monomer stainless steel (MSS) roof panels and continuous welded stainless steel (CWSS) roof panels are investigated. The MSS roof panels are considered different surface roughness, horizontal inclination angle and spatial location, and the CWSS roof panels are studied the influence of horizontal inclination angle and spatial location. Based on the test result, the temperature field and variations of the roof panels in a typical day, different light intensities, and wind speeds are analyzed in detail. Numerical simulation is further used to compare with the experimental results. The overall and local stress and deformation characteristics of the CWSS roof are analyzed, and relevant design improvement is proposed. The feasibility of a simplified temperature calculation approach for CWSS roof panels is verified by experimental and numerical results. The experimental and numerical study demonstrates that the temperature field and thermal effects on roof panels are significant. The maximum temperature of the roof panels reached 56.8 °C, and the maximum temperature difference is 28.3 °C compared with ambient air temperature. The temperature stress can reach 65.8% of the yield strength, and the temperature deformation can reach 1/1600 of the roof span, which will be more obvious in the practical roof system. •Solar temperature field and variations test of MSS and CWSS roof panels are conducted.•The time-varying distribution regularities under different thermal conditions are analyzed contrastively.•Numerical simulation is further used to compare with the experimental results.•The thermal effects of the continuous welded stainless steel roof are analyzed, and relevant design improvement is investigated.•A simplified formula for calculating the temperature of the roof panels is proposed.